2005
DOI: 10.1111/j.1572-0241.2005.41350.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoreceptors of the Proximal Stomach and Perception of Gastric Distension

Abstract: Our data do not support a prominent role of tension receptors of the proximal stomach on perception of fullness, suggesting that stretch, that is, volume, is the more relevant stimulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Studies in humans have shown that changes in gastric muscle tone evoked by glucagon or erythromycin do not markedly affect the sensation of fullness evoked by a distension of fixed volume 155 . This finding suggests that volume, rather than pressure or wall tension, is sensed by afferents that mediate fullness.…”
Section: Extrinsic Afferent Pathways and Sensationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in humans have shown that changes in gastric muscle tone evoked by glucagon or erythromycin do not markedly affect the sensation of fullness evoked by a distension of fixed volume 155 . This finding suggests that volume, rather than pressure or wall tension, is sensed by afferents that mediate fullness.…”
Section: Extrinsic Afferent Pathways and Sensationmentioning
confidence: 99%
“…This finding suggests that volume, rather than pressure or wall tension, is sensed by afferents that mediate fullness. 155 It has been argued, on the basis of anatomical considerations, that there must be specialized volume receptors in the stomach that encode distension, largely independent of wall tension or pressure. However, to date, electrophysiological studies have failed to record specific length-sensitive extrinsic afferents.…”
Section: Extrinsic Afferent Pathways and Sensationmentioning
confidence: 99%
“…According to the simplified law of Laplace, increased intragastric pressure will be associated with increased wall tension for the same intragastric volume. Studies using isovolumetric and isobaric gastric distensions indicate that gastric wall tension receptors may be most relevant for mediating distension‐induced sensation 53, 54 . In fact, by using a tensostat that keeps an intragastric bag at a constant tension (calculated according to the simplified Laplace’s law) it was shown that sensations from the proximal stomach depend on gastric wall tension, whereas intragastric volume and expansion seem less relevant 55 …”
Section: Satiation During Food Intakementioning
confidence: 99%
“…As the gastric wall undergoes receptive relaxation or accommodates, the smooth muscle fibers relax and lengthen, thus increasing the circumference of the organ so that the volume of ingested material is accepted and stored temporarily, with minimal to no change in tension. Stretch and tension not only are uncoupled in this situation, the two forces can actually independently affect different perceptions and responses (see, e.g., Notivol et al, 1995;Penagini et al, 2004;Carmagnola et al, 2005).Similarly, in the case of the antrum, with its adaptations for triturating and emptying digesta into the duodenal bulb, tension and stretch can be uncorrelated. Because gastric contents vary in consistency, they can vary in the resistance or tension that they generate, while the circumference of the antral lumen (i.e., stretch or length of the muscle sheets) does not necessarily covary.…”
mentioning
confidence: 99%